2020
DOI: 10.5664/jcsm.8346
|View full text |Cite
|
Sign up to set email alerts
|

Use of positive airway pressure in mild cognitive impairment to delay progression to dementia

Abstract: Study Objectives: The aim was to assess the relationship between continuous positive airway pressure (CPAP) therapy and cognitive function in patients with mild cognitive impairment (MCI) and obstructive sleep apnea (OSA). Methods: This was a retrospective chart review of patients with MCI and OSA. CPAP therapy compliance was defined as average use of CPAP therapy for at least 4 hours per night. Kaplan-Meier estimates, log-rank tests, and Cox proportional hazards regression were done to compare the compliance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Of the 11 identified studies, 6 considered apnea-hypopnea index (AHI) a measure for OSA severity (AHI ≥10, mild to severe 21,24,26 ; AHI 10–14, mild 25 ; and AHI ≥30, severe 28 ) and all levels of OSA severity. 13 Baseline cognitive impairment (MCI or AD) was present among 9% (n = 5,826) of study participants. Data extraction summaries are reported in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 11 identified studies, 6 considered apnea-hypopnea index (AHI) a measure for OSA severity (AHI ≥10, mild to severe 21,24,26 ; AHI 10–14, mild 25 ; and AHI ≥30, severe 28 ) and all levels of OSA severity. 13 Baseline cognitive impairment (MCI or AD) was present among 9% (n = 5,826) of study participants. Data extraction summaries are reported in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…13,21,24-28 In US-based studies, participants were predominantly White (range 59%–98%), and across all studies, the proportion of women ranged between 25% and 53%. Six studies included both middle-aged and older participants, 13,23-25,27,29 while 5 focused on older adults (≥65 years of age). 14,21,22,26,28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the paper from Skiba et al 1 about the effect of obstructive sleep apnea (OSA) treatment by continuous positive airway pressure (CPAP) in patients with mild cognitive impairment. Treating OSA in patients at risk of Alzheimer disease (AD) is a hot research topic, considering that OSA can represent a risk factor for AD, accelerate cognitive decline, and contribute to alter AD pathology biomarkers (eg, clinical, biofluid, neuroimaging).…”
mentioning
confidence: 99%
“…In line with these findings, another recent retrospective study [ 70 ], considering a large sample of patients diagnosed with OSA, documented that PAP adherence was associated with lower odds of incident diagnoses of AD. Conversely, Skiba et al [ 71 ] reported no significant differences between CPAP compliant, CPAP non-compliant and no CPAP use on a sample of 96 MCI patients. However, when looking at the timing before conversion, it appeared evident that patients CPAP compliant (77.3 months) presented a longer time before conversion than non-compliant (52.1 months) or non-use (47.3 months) CPAP groups.…”
Section: The Effects Of Cpap Therapy On Cognitionmentioning
confidence: 99%